ANALISIS EFISIENSI FAKTOR PRODUKSI USAHATANI PADI SAWAH SRI ORGANIK DAN AN-ORGANIK DI DESA KELAYANG KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Khairizal Khairizal; Azharuddin Azharuddin (UIR Press, 2014)
Achievement of efficiency levels in business management determines the success of paddy farming organic and an-organic in order to produce products that can compete in the market and provide income for rice farmers of organic and un-organic. This study aimed to analyze the level of technical efficiency, the price/allocative efficiency and economic efficiency of organic and an-organic rice farming. The analysis models used the Production Function Stochastic Frontier Analysis (SFA). The study was conducted by a census method for organic farmers and a random sampling method for un-organic farmers located in the Rakit Kulim Village, Kelayang District, Indragiri Hulu Regency. The amount of organic rice farmers was 35 and the number of samples of rice farmers un-organic was 45 farmers for a total of 272 farmers. The results show the value of Technical Efficiency (ET) organic rice paddy averaged 0.9395/land size (0.3612 ha), while the value of 0.8299 an-organic rice ET/land size (0.387 ha). Allocative efficiency/price (EA) for the organic rice was 102.96/land size, while the value of rice farming EA un-organic was 0.18/land size. The value of the Economic Efficiency (EE) for organic rice farming was 96.68/land size and value of EE on un-organic rice farming was 0.15 per hectar.